In-vitroculture of Ophiocordyceps sinensis (Yarsagumba) and their associated endophytic fungi of Nepal Himalaya - Baral, Bikash; Maharjan, Jyoti (Scientific World, 2012)
An array of Ophiocordyceps sinensis and its associated endophytic fungi residing in the high Nepalese meadows were isolated and studied for their association and symbiotic effectiveness with the host plant. Fungi are noted to be quite common in nature and some of them have been shown to have adverse effects against insects, nematodes and plant pathogens. Out of the few isolates, different types of associated fungi with Ophiocordyceps sinensis were screened viz. Acremonium strictum, Altenaria solani, Aspergillus flavus, Trichoderma virens, Colletotrichum gloeosporiode, Curvularia lunata, Thielaviopsis sp. and Verticillium sp. The growth rate of the Ophiocordyceps sinensis was found to be very slow as compared to other associated fungi with the diameter of only 1 cm in 2 weeks interval. Fast growing endophytic fungi was found to be Acremonium strictum followed by Altenaria solani. However, the maintenance of the pure culture of the Ophiocordyceps fungi is rather difficult and was soon covered up with other associated fungi. Besides, it was rather difficult to sporulate the O. sinensis in the laboratory conditions despite using specific medias. Scientific World, Vol. 10, No. 10, July 2012 p38-42 DOI: http://dx.doi.org/10.3126/sw.v10i10.6860